Implementasi Program Fundraising Berkala Baik pada Organisasi Nirlaba Janji Baik - Muhamad Sofiyudin; Tuti Alawiyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Many nonprofit organizations in Indonesia face challenges in managing resources, operations, and Fundraising strategies, particularly in maintaining financial stability. Only about 13% have sustainable financing strategies, making this study relevant to evaluate the Fundraising model implemented by a nonprofit organization. This research analyzes the implementation of the “Berkala Baik” Fundraising program at the Janji Baik nonprofit organization, focusing on organizational management, functional strategies, and the supporting and inhibiting factors of the program. The study employs a qualitative case study approach with data collected through in-depth interviews, participant observation, and documentation review. Data analysis involves reduction, presentation, conclusion drawing, and triangulation validation. The findings indicate that Janji Baik operates under the Baik Media Indonesia Foundation, focusing on education, social welfare, and technology. The Berkala Baik program is an innovation for sustainable funding through monthly donations over one year (ranging from IDR 25,000 to IDR 100,000) accompanied by exclusive merchandise. Fundraising strategies include membership systems, volunteer engagement, campaigns, and special events. Supporting factors consist of timely member payments, high public interest, and active volunteer participation. Inhibiting factors include delayed donations, limited public understanding of Fundraising concepts, and communication challenges. This study is expected to enrich the literature and practical insights on nonprofit management and Fundraising practices in Indonesia.